2021
DOI: 10.1021/acsaem.1c01420
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Composite Gel Polymer Electrolytes with High Thermal Conductivity toward Wide Temperature Lithium Metal Batteries

Abstract: Herein, the thermally conductive composite polymer membranes (CPMs) with silica-coated silver nanowires (AgNWs@SiO2) and poly­(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) are first fabricated by an electrospinning technique. Various composite gel polymer electrolytes (CGPEs) are investigated with different weight percentages of AgNWs@SiO2 with respect to PVDF-HFP in the presence of liquid electrolytes. The CPMs display high thermal conductivity and thermal stability, good mechanical strength, and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The silver nanowires (AgNWs), AgNWs@SiO 2 and PVDF-HFP/AgNWs@SiO 2 CPMs were prepared according to our previous work. [20] The 0 wt % or 5 wt % of AgNWs@SiO 2 with respect to that of PVDF-HFP in acetone/DMF solution (7 : 3, w/w) and the concentration was 12 wt %. Then, the electrospinning was performed using a 10 mL of syringe by the stainless-steel needle with a 13 kV applying voltage.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The silver nanowires (AgNWs), AgNWs@SiO 2 and PVDF-HFP/AgNWs@SiO 2 CPMs were prepared according to our previous work. [20] The 0 wt % or 5 wt % of AgNWs@SiO 2 with respect to that of PVDF-HFP in acetone/DMF solution (7 : 3, w/w) and the concentration was 12 wt %. Then, the electrospinning was performed using a 10 mL of syringe by the stainless-steel needle with a 13 kV applying voltage.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, inorganic nanofillers (Al 2 O 3 , SiO 2 , and Li 6.4 La 3 Zr 2 Al 0.2 O 12 ) have widely been employed for enhancing of mechanical strength and electrochemical performance of polymer electrolyte or separator. [16][17][18][19][20] It is well-known that the silver nanowires (AgNWs) have been served for the application in the field of energy and storage devices owing to their superior high electrical and thermal conductivities, good photo-thermal properties, high aspect ratio, and one-dimensional structure. [20][21][22][23][24][25] However, it is hardly reported that the AgNWs were considered as nanofillers in polymer electrolyte or separator.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhancing the thermal conductivity of the separator can promote heat dissipation and relieve thermal stress caused by temperature inhomogeneity. Very recently, Xue et al fabricated composite polymer membranes using the electrospinning technology based on silica-coated silver nanowires and poly­(vinylidene fluoride-hexafluoropropylene) for use in LIBs, demonstrating their enhanced thermal stability, thermal conductivity, and electrochemical properties . Ceylan et al reported an electrospinning technique to fabricate polyacrylonitrile and poly­(methyl methacrylate) nanocomposite fibers loaded with graphene nanoplatelets to improve the thermal management of LIBs .…”
Section: Introductionmentioning
confidence: 99%